نظرية بناء مثنى المبهمات على الألف عند أبن تيمية : دراسة وصفة تحليلية - عبدالقادر، هاجر سليمان طه (جامعة السودان للعلوم والتكنولوجيا - معهد العلوم والبحوث الإسلامية, 2014)
ناقش هذا البحث نظرية ابن تيمية في بناء مثنى المبهمات على الألف، فشرحت الدراسة النظرية وناقشتها مبينة عوامل القوة والضعف فيها، هدفت الدراسة إلى بيان هذه النظرية باعتبارها مغايرة لما هو مشهور في إعراب المبهمات المثناة. خلصت الدراسة إلى أن لابن تيمية جهود مقدرة في علم النحو العربي، كما توصلت إلى أن هذه النظرية جديرة بمزيد من الدراسة في ضوء القواعد المشهورة في بابها ما يؤدي إلى إثراء الدرس النحوي واللغوي. This study discusses the theory of Ibn Tayimya on dual abstract nouns saying that they must always have a constant vowel of /a/ (alif) regardless of the context. The study explains and discusses the theory stating its strengths and weaknesses. It aims at stating that this theory is distinct from what is common about the parsing of dual abstract nouns. It has been concluded that Ibn Tayimya has great valuable efforts in Arabic Grammar. The study has also concluded that this theory deserves to be studied more and more in terms of the famous rules in this area so as to enrich the linguistic and grammar lesson.
Keywords: النحو -- النحاة -- اللغة العربية -- علماء اللغة العربية -- الدراسات النظرية -- تفسير القرآن